2019
DOI: 10.1158/1078-0432.ccr-18-2906
|View full text |Cite
|
Sign up to set email alerts
|

YH25448, an Irreversible EGFR-TKI with Potent Intracranial Activity in EGFR Mutant Non–Small Cell Lung Cancer

Abstract: Purpose: Given that osimertinib is the only approved thirdgeneration EGFR-TKI against EGFR activating and resistant T790M mutated non-small cell lung cancer (NSCLC), additional mutant-selective inhibitors with a higher efficacy, especially for brain metastases, with favorable toxicity profile are still needed. In this study, we investigated the antitumor efficacy of YH25448, an oral, mutant-selective, irreversible third-generation EGFR-TKI in preclinical models.Experimental Design: Antitumor activity of YH2544… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 38 publications
5
80
0
Order By: Relevance
“…Moreover, nowadays, there are advanced novel immunotherapies and targeted therapies that was reported to show increased blood–brain barrier penetration and realize high response rates and more durable control of BM, and advances in radiotherapies and minimally invasive surgical techniques, which are thought to improve the survival outcome of patients with BM 7,17 . For example, EGFR/ALK TKIs had significant intracranial activity and could achieve longer intracranial progression free survival, higher overall response rate than chemotherapy or radiotherapy, which have been proved in many retrospective and prospective studies 18–22 . And some studies have confirmed that stereotactic radiotherapy (SRS) was a well‐tolerated safe option for patients with four or more BM 23–25 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, nowadays, there are advanced novel immunotherapies and targeted therapies that was reported to show increased blood–brain barrier penetration and realize high response rates and more durable control of BM, and advances in radiotherapies and minimally invasive surgical techniques, which are thought to improve the survival outcome of patients with BM 7,17 . For example, EGFR/ALK TKIs had significant intracranial activity and could achieve longer intracranial progression free survival, higher overall response rate than chemotherapy or radiotherapy, which have been proved in many retrospective and prospective studies 18–22 . And some studies have confirmed that stereotactic radiotherapy (SRS) was a well‐tolerated safe option for patients with four or more BM 23–25 .…”
Section: Discussionmentioning
confidence: 94%
“…Novel targeted therapies have demonstrated preclinical CNS results that may support a role in the treatment or prevention of IMD, with improved selectivity for EGFR alterations and reduced CNS efflux compared with osimertinib. 60,61 In addition, innovation in therapeutic delivery modalities may guide treatment sequencing or support the use of existing systemic treatments, which have historically been limited by their lack of BBB permeability. Methods of increasing BBB penetrance of systemic drugs include modification through rational drug design, conjugation to ligands targeted to receptor-mediated transport, and disruption of the BBB through the use of osmotic media, biochemical agents, focused ultrasonography, or radiotherapy.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…Lazertinib is an oral, potent, irreversible third-generation EGFR TKI that is highly selective for activating EGFR and T790M resistance mutations. In pre-clinical studies, lazertinib induced profound tumour regression in a brain metastasis model with favourable brain/plasma and tumour/ brain area under the concentration-time curve values (39).…”
Section: Lazertinib (Yh25448/gns-1480)mentioning
confidence: 98%